Arthroscopic treatment of glenohumeral instability in soccer goalkeepers - Terra, B. B.; Ejnisman, B.; Figueiredo, E. A.; Andreoli, C. V.; Pochini, A. C.; Cohen, C.; Arliani, G. G.; Cohen, M. (International Journal of Sports Medicine, 2013)
The aim of this study was to report epidemiologic data and results of arthroscopic treatment of glenohumeral instability in soccer goalkeepers. We included 12 soccer goalkeepers with a mean age of 28.9 years (range 18-45 years) with acute or recurrent traumatic anterior instability who underwent an arthroscopic anatomic capsulolabral repair with bone anchors. Patients who underwent surgery within 4 weeks of the first episode of dislocation were classified as acute instability. The results were evaluated using the Rowe Scale and analyzed according to stability, range of motion and function. The mean follow-up was 3.8 years. The most common mechanism of injury (90% of the cases) was abduction, external rotation and extension. Associated injuries were present in 57.2% of recurrent cases and 20% of acute cases (p<0.293). Excellent or good results were observed in 80% of the cases of acute instability and in 57.2% of cases in the group with recurrent instability (p<0.586). From a total of 12 soccer goalkeepers who underwent the arthroscopic capsulolabral repair, good or excellent results were obtained in 66.6% of cases of glenohumeral instability. Surgical arthroscopic repair was possible in all cases of acute or recurrent instability based on well-established inclusion criteria, i. e., with well-defined exclusion criteria, such as HAGL lesion and significant glenohumeral bone loss, the arthroscopic capsulolabral repair can be carried out in soccer goalkeepers.